Effectiveness and ecumenicity - Lim, Chong-Ming (2020)
Effective altruism is purportedly ecumenical towards different moral views, charitable causes, and evidentiary methods. I argue that effective altruists’ criticisms of purportedly less effective charities are inconsistent with their commitment to ecumenicity. Individuals may justifiably support charities other than those recommended by effective altruism. If effective altruists take their commitment to ecumenicity seriously, they will have to revise their criticisms of many of these charities.